The Effect of Strength Training on Performance Indicators in Distance Runners - Beattie, Kris; Carson, Brian P; Lyons, Mark; Rossiter, Antonia; Kenny, Ian C (Journal of strength and conditioning research, 2017)
Beattie, K, Carson, BP, Lyons, M, Rossiter, A, and Kenny, IC. The effect of strength training on performance indicators in distance runners. J Strength Cond Res 31(1): 9-23, 2017-Running economy (RE) and velocity at maximal oxygen uptake (VV[Combining Dot Above]O2max) are considered to be the best physiological performance indicators in elite distance runners. In addition to cardiovascular function, RE and VV[Combining Dot Above]O2max are partly dictated by neuromuscular factors. One technique to improve neuromuscular function in athletes is through strength training. The aim of this study was to investigate the effect of a 40-week strength training intervention on strength (maximal and reactive strength), VV[Combining Dot Above]O2max, economy, and body composition (body mass, fat, and lean mass) in competitive distance runners. Twenty competitive distance runners were divided into an intervention group (n = 11; 29.5 ± 10.0 years; 72.8 ± 6.6 kg; 1.83 ± 0.08 m) and a control group (n = 9; 27.4 ± 7.2 years; 70.2 ± 6.4 kg; 1.77 ± 0.04 m). During week 0, 20, and 40, each subject completed 3 assessments: physiology (V2 mmol·L BLa, V2 mmol·L BLa [blood lactate], V4 mmol·L BLa, RE, VV[Combining Dot Above]O2max, V[Combining Dot Above]O2max), strength (1 repetition maximum back squat; countermovement jump and 0.3 m drop jump), and body composition (body mass, fat mass, overall lean, and leg lean). The intervention group showed significant improvements in maximal and reactive strength qualities, RE, and VV[Combining Dot Above]O2max, at weeks 20 (p ≤ 0.05) and 40 (p ≤ 0.05). The control group showed no significant changes at either time point. There were no significant changes in body composition variables between or within groups. This study demonstrates that 40 weeks of strength training can significantly improve maximal and reactive strength qualities, RE, and VV[Combining Dot Above]O2max, without concomitant hypertrophy, in competitive distance runners.